Prenylated flavonoid morusin protects against TNBS-induced colitis in rats - Vochyánová, Zora; Pokorná, Marie; Rotrekl, Dominik; Smékal, Václav; Fictum, Petr; Suchý, Pavel; Gajdziok, Jan; Šmejkal, Karel; Hošek, Jan (PloS one, 2017)
Morusin is a prenylated flavonoid isolated from the root bark of Morus alba. Many studies have shown the ability of flavonoids to act as anti-inflammatory agents. The aim of this study was to evaluate the effect of morusin on experimentally colitis induced by 2,4,6-trinitrobenzensulfonic acid in Wistar rats and to compare it with sulfasalazine, a drug conventionally used in the treatment of inflammatory bowel disease. Morusin was administered by gavage at doses of 12.5, 25, or 50 mg/kg/day for five days. The colonic tissue was evaluated macroscopically, histologically, and by performing immunodetection and zymographic analysis to determine the levels of antioxidant enzymes [superoxide dismutase (SOD) and catalase (CAT)], interleukin (IL)-1β, and transforming growth factor (TGF)-β1 and the activities of matrix metalloproteinases (MMP) 2 and 9. The tissue damage scores were significantly reduced with increasing dose of morusin, however efficacy was not demonstrated at the highest dose. At the dose of 12.5 mg/kg, morusin exerted therapeutic effectivity similar to that of sulfasalazine (50 mg/kg). This was associated with significant reduction of TGF-β1 levels and MMP2 and MMP9 activities, and slight reduction of IL-1β. Our results suggest that morusin possesses therapeutic potential for the treatment of chronic inflammatory diseases.
Keywords: Colitis; kyselina trinitrobenzensulfonová; kolon; Male; Flavonoids; Trinitrobenzenesulfonic Acid; kolitida; Animals; Rats, Wistar; mužské pohlaví; matrixová metaloproteinasa 2; flavonoidy; potkani Wistar; prenylace; Matrix Metalloproteinase 2; Prenylation; zvířata; Colon